16 The Statutes at Large of Pennsylvania from 1682 to 1801, at 297 (1911) - (:unkn) unknown (My University, 1799)
Explicitly allowed "sons who are not subject to the militia law may be admitted as substitutes for their fathers."
Keywords: MILITIAS